The Effect of Arm Muscle Explosion and Student’s Learning Motivation on Volleyball Service Ability of Students - Dahlia, Dahlia; Kristina, Putri Cicilia; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to find out how much influence the explosive power of the arm muscles and students’ learning motivation had on the ability to serve in volleyball. The method used in this research is literature review. The relationship between student learning motivation and student learning outcomes in volleyball games and the explosive power of the arm muscles that support the ability to serve volleyball as well as the instruments commonly used to measure learning motivation and the explosive power of the arm muscles. The results showed increasing students’ learning motivation towards volleyball games really needs to be improved because volleyball games can indirectly have many benefits for students, including good for physical fitness, can form good personality or behavior because volleyball games require good mentality, can form character and foster a quick mindset in making decisions. The low learning outcomes of students in physical education subjects, especially in big volleyball games, are suspected to be due to poor upper serve skills, where when doing the top serve there are still many students who serve unable to cross the net, have not been able to land the ball at target, the ball often comes out and concerns the net. Service is a very important technique in volleyball game because service is the beginning of the game. In this study, we will discuss about the top serve in volleyball because high school/vocational high school students in volleyball games should use the top serve. To support the ability to serve over in volleyball, arm muscle explosive power is needed. The explosive power of the arm muscles is a very important physical condition needed in mastering the volleyball serve.